Determination of flower biology of pollinator attracting underexploited vegetable, Luffa cylindrica (L.) growing in home gardens of Jaffna - Sathyakala, K.; Mikunthan, G. (2nd International Conference on Agriculture and Forestry, ICOAF, 2015)
Luffa cylindrica is an edible, underexploited, Cucurbitaceae vegetable crop in Sri Lanka. It has the potential to attract diverse pollinators and to sustain their visits to the home gardens. Conserving the pollinator diversity through the sustained contribution of potential plants that support pollinators in the home gardens were studied. Flower biology of L. cylindrica was investigated by assessing the flowering stages over time, corolla opening with time, maximum nectar production, anthesis, pollen shedding time and stigma receptivity. The rate of flower opening was at peak around 03.45 hr to 04.15 hr. Anthesis was prolonged for 2-21/2 hours and stigma receptivity was 3-31/2 hours after flower opening fully. The nectar volume appeared to be the highest around 6 hr after flower opening. Of the L. cylindrica flower visitors, nine bee species (Amegilla sp, Amegilla cingulata, Apis florea, Apis cerana, Ceratina binghami, Trigona iridipennis, Thyreus ramosellus and Lasioglossum vagans, Xylocopa fenestrata), three butterfly species (Catopsilia pyranthe, Telchinia violae and Appias paulina) and an ant were found. These results confirm the potential of L. cylindrica to be grown as one of the pollinator conserving plant in the home gardens of Jaffna